PENGELOLAAN SAMPAH PLASTIK DAN RT DI KELURAHAN PENATIH KECAMATAN DENPASAR TIMUR MENUJU BIOENTREPRENEUSHIP - Suanda, I Wayan; Ayu Rai, I Gusti; Purnamasari, Ni Putu Laras; Alit, Dewa Made; Rusmayanthi, Kadek Intan (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
Plastic waste and household waste generated by the community have not been able to be handled properly. The existence of waste cannot be separated from the impact of community activities and economic growth. Suboptimal waste handling can cause a less clean view, a nesting place for mosquitoes and germs that cause diseases, disrupt health, damage the environment, block the water flow and other negative impacts. The results of the observations from the devotion Lecturer Team have found the existence of plastic waste and household waste have not been handled optimally and have a negative impact on health and the environment. Although there is a waste bank, it has not been able to handle it optimally, so another solution that is more economically beneficial is needed. Therefore, we from the team of lecturers and students of PGRI Mahadewa University Indonesia and Ngurah Rai University Denpasar contributed through community service activities in the form of Socialization and Assistance for Plastic and Household Waste Management to the Community in Penatih Village, East Denpasar District, Denpasar City. The purpose of this community service is waste management from the source, namely community-based households as self-management to be used as an activity and has a useful value.